Identity and the spoken grammar dilemma. (June 2015) - Soruç, Adem; Griffiths, Carol
Abstract: This article reports on a study that investigated issues involved with the teaching of features of spoken English, sometimes called spoken grammar, including the use of vague language, placeholders, lexico-grammatical units and ellipsis. Materials focussing on four spoken features were prepared and presented over a period of two months to 19 students aged 18 to 20 preparing to enter a private university in Istanbul, Turkey. Of these students, nine were female and 10 male. It was found that although some initial uptake of these features was evident at the time of the post-test, little had been maintained by the time of the delayed post-test three weeks later. During focus group interviews, students attributed this attrition to the fact that spoken grammar norms conflicted with their own sense of identity, making them feel "fake", "artificial" and "embarrassed". The dilemma regarding the perceived pedagogical need to teach "natural" English by native speaker norms, versus students' need to adopt features with which they feel comfortable according to their own sense of identity is discussed. It is suggested that teaching spoken grammar should be seen as offering learners choices which they are free to adopt or not according to their own identities.